The Relationship Between Energy Intake, Protein Intake, and the Albumin-To Globulin Ratio and Stunting in Toddlers Aged 24–59 Months - Hafsha Rizki (Eduvest - Journal of Universal Studies, 2026)
Stunting remains a global public health problem characterized by chronic growth failure resulting from long-term undernutrition and recurrent infections. This study aims to analyze the relationship between energy intake, protein intake, and the albumin-to-globulin (A/G) ratio and the incidence of stunting in toddlers aged 24–59 months. The study synthesized evidence from 18 expert-validated variables derived from the literature in the fields of nutrition, public health, and immunometabolism. Energy and protein intake were assessed alongside serum biomarkers, including albumin, globulin, and the A/G ratio, while stunting status was determined based on the Height-for-Age Z-score (HAZ) according to World Health Organization (WHO) standards. The literature review findings demonstrated that low energy and protein intake, together with a decreased A/G ratio, were significantly associated with the incidence of stunting. These findings indicate that inflammatory and metabolic imbalances, as reflected by serum protein biomarkers, play an important role in growth disorders in addition to inadequate nutritional intake. Stunting is not solely caused by an energy deficit but also involves complex biological mechanisms, including chronic inflammation and disturbances in protein metabolism. This study contributes to a more integrative understanding of stunting by combining nutritional and biomolecular perspectives while supporting the development of more precise and multidimensional intervention strategies.